The Influence of Tourist Attractions and Promotional Strategies on The Decision to Visit the Golomori Tourist Area - Dayan Hakim; Taufik Hidayat; Ekos Albar; Listri Herlina (Jurnal Manajemen, 2026)
PT Pengembangan Pariwisata Indonesia (Persero)/ITDC acquired approximately 20 hectares of HGB land in Golo Mori, Komodo District, East Nusa Tenggara in 2021, following the Decree of the Minister of State-Owned Enterprises regarding the acceleration of the Golomori Special Economic Zone development. This study employed a quantitative approach to examine the influence of tourist attractions and promotional strategies on the decision to visit the Golomori Tourism Area. Findings indicate that tourist attractions significantly influence visit decisions, supported by natural scenery, authentic cultural narratives, and adequate facilities, though location layout requires further innovation. Promotional strategies also significantly influence visit decisions, particularly through social media and special events, although collaboration with travel agencies remains suboptimal. Simultaneously, both variables significantly influence visit decisions. This means that these two variables are able to explain a large portion of the variation in tourists' decisions to visit the Golomori Tourism Area.